2018
DOI: 10.1039/c8ra00436f
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of pore structure in mesoporous carbon for favourable flavin mediated interfacial electron transfer in microbial fuel cells

Abstract: Mesoporous carbon (MC) is supposed to be a good candidate for microbial fuel cell (MFC) anodes as it possesses a large specific area for the redox reaction of the electron shuttles and should deliver high power density. However, the power generation performance of MC anodes is often un-satisfying. It seems that a large portion of the pore surface is not available for anodic redox reaction but the reason is not clear. Here, three MCs with different pore sizes and pore shapes were fabricated and used to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Polymers 2020, 12, x FOR PEER REVIEW 2 of 11 ordered mesoporous carbon [12]. However, the effect of hierarchical porous structure with different proportion of meso-and macro-pores on the flavin based interfacial electron transfer process is not very clear.…”
Section: Of 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers 2020, 12, x FOR PEER REVIEW 2 of 11 ordered mesoporous carbon [12]. However, the effect of hierarchical porous structure with different proportion of meso-and macro-pores on the flavin based interfacial electron transfer process is not very clear.…”
Section: Of 11mentioning
confidence: 99%
“…In this case, appropriate porous structure of the MFC anode are essential for the flavin based interfacial electron transfer. In our previous work, it has been demonstrated that the size and curvature of mesopores are critical for the redox reaction of the endogenous flavin mediators in bacteria cellulose derived carbon fibers [11] and sucrose derived ordered mesoporous carbon [12]. However, the effect of hierarchical porous structure with different proportion of meso-and macro-pores on the flavin based interfacial electron transfer process is not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the mesopores (pore width 2-50 nm) are more favorable for flavin-based IET in Shewanella sp. catalyzed MFCs than the micropores (pore width less than 2 nm) [3,4]. The open mesopores with appropriate pore size and pore shape could provide suitable space for the two-electron oxidation of the flavins on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%